Antibiotic prophylaxis of purulent and septical complications during surgical treatment of complicated gallstone disease on background of liver cirrhosis - Khimich, S. D.; Muravyev, F. T. (Modern medical technology, 2019)
Purpose of the study. The goal of this investigation was to determine the main risk factors in development of purulent and septical complications during surgical treatment of complicated gallstone disease on background of liver cirrhosis. Materials and methods. We retrospectively reviewed medical records of 247 patients who undergone treatment in minimally invasive surgery centre of Zhytomyr regional clinical hospital during 2009–2018. All patients with complicated gallstone disease were divided in two groups: group 1 – patients with concomitant liver cirrhosis – 79(31,98%), and group 2 – patients without liver cirrhosis – 168 (68,02%). Theinclusion criteria were presents of complicated gallstone disease (acute calculous cholecystitis, choledocholithiasis with obstructive jaundice and Mirizzi syndrome), and verified liver cirrhosis. Patients with oncological history, immunodeficiency and morbid obesity were excluded. Liver cirrhosis was staged by Child-ТurcotteРugh system. In all cases patient’s condition was assessed by APACHE II scoring system and patients with cirrhotic lesion were additionally analyzed by MELD score. Acute calculous cholecystitis was diagnosed in 185 patients: group 1 – 68(Child A – 36, Child B – 31, Child C – 1), group 2 – 117 patients. The signs of cholodecholithiasis with obstructive jaundice were present in 49 cases: group 1 – 7 (Child A – 5, Child B – 1, Child C – 1), group 2 – 42. Mirizzi syndrome was verified in 9 cases: group 1 – 2 (Child A – 1, Child B – 1, group 2 – 7. Results and discussion. In all patients treatment was started in conservative way that included detoxic, antibacterial and hepatoprotective components. In group of control early operative tactic in cases with acute calculous cholecystitis was preferred. Antimicrobial prophylaxis was performed in cases of severe and moderate calculous cholecystitits with use of cephalosporines of 2 generation in moderate case, and protected cephalosporines of 3 generation in combination with metronidazol in severe. In main group providing of antimicrobial therapy was performed very carefully, because of higher risk of hepato-renal insufficiency. The early de-escalation therapy was mandatory performed. Purulent complications occurred in 13,2% of patient with liver cirrhosis in comparison with control group with 1,7% of complications. Conclusion. The treatment of complicated gallstone disease in patients with liver cirrhosis is very risky in case of postoperative purulent complications. In case of Child A stage of cirrhosis the treatment is safe, and the incidents of purulent complications is the same like in the absence of cirrhosis. Administration of antibiotics in cirrhotic should be very careful because of higher risk of hepato-renal insufficiency. The early de-escalation therapy should be mandatory performed. The «gold» standard of empirical antimicrobial therapy is the use of cephalosporines of 2 and 3 generation.